2014
DOI: 10.1371/journal.pone.0112329
|View full text |Cite
|
Sign up to set email alerts
|

Primates Living Outside Protected Habitats Are More Stressed: The Case of Black Howler Monkeys in the Yucatán Peninsula

Abstract: The non-invasive monitoring of glucocorticoid hormones allows for the assessment of the physiological effects of anthropogenic disturbances on wildlife. Variation in glucocorticoid levels of the same species between protected and unprotect areas seldom has been measured, and the available evidence suggests that this relationship may depend on species-specific habitat requirements and biology. In the present study we focused on black howler monkeys (Alouatta pigra), a canopy-dwelling primate species, as a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…Additionally, although glucocorticoids have been linked to energy expenditure in this population (Dias et al, ), which was further confirmed in this study by their negative correlation with thyroid hormone levels, they are also associated with other factors, such as social challenges. Participation in agonistic interactions and glucocorticoid levels have been found to co‐vary in this and in other howler monkey species (Dias et al, ; Gómez‐Espinosa et al, ; Rangel‐Negrín, Coyohua‐Fuentes, Chavira‐Ramírez, Canales‐Espinosa & Dias, ). Therefore, variation in female exposure to psychosocial challenges could account for some of the observed variation in both conception probabilities and IBI.…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, although glucocorticoids have been linked to energy expenditure in this population (Dias et al, ), which was further confirmed in this study by their negative correlation with thyroid hormone levels, they are also associated with other factors, such as social challenges. Participation in agonistic interactions and glucocorticoid levels have been found to co‐vary in this and in other howler monkey species (Dias et al, ; Gómez‐Espinosa et al, ; Rangel‐Negrín, Coyohua‐Fuentes, Chavira‐Ramírez, Canales‐Espinosa & Dias, ). Therefore, variation in female exposure to psychosocial challenges could account for some of the observed variation in both conception probabilities and IBI.…”
Section: Discussionmentioning
confidence: 59%
“…Previous research indicated that the glucocorticoid levels of howler monkeys could be affected by energetic and psychosocial stressors (Crist obal-Azkarate et al, 2007;Dunn et al, 2013;G omez-Espinosa et al, 2014), as well as by living in either extensive or fragmented forests (Mart ınez- Mota et al, 2007;Rangel-Negr ın et al, 2014b). We therefore modeled variation in maternal glucocorticoids as a function of habitat type (females in five groups in extensive vs. females in five groups in fragmented forests), the amount of time spent traveling (a proxy for energetic stress), and participation in agonistic social interactions (a proxy for psychosocial stress).…”
Section: Discussionmentioning
confidence: 99%
“…The glucocorticoid levels of howler monkeys are generally higher in fragmented than in extensive forests as a consequence of low food availability, high anthropogenic pressures and both high feeding and reproductive competition (Crist obal- Azkarate et al, 2007;Mart ınez-Mota et al, 2007;Dunn et al, 2013;G omez-Espinosa et al, 2014;Rangel-Negr ın et al, 2014b). Therefore, glucocorticoid elevation in forest fragments signals a myriad of adverse environmental conditions that may have negative consequences for infant survival, and as a consequence, female reproductive success (Dias et al, 2015a(Dias et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In general, anthropogenic changes to primate habitats impact primate populations by changing the availability, density, abundance, and distribution of plant species (Milich, Stumpf, Chambers, & Chapman, ) which in turn, can trigger a physiological stress response reflected in higher cortisol levels (e.g., Alouatta pigra (Arroyo‐Rodriguez & Dias, ; Martínez‐Mota, Valdespino, Sánchez‐Ramos, & Serio‐Silva, ), Piliocolobus tephrosceles (Chapman, Saj, & Snaith, ), L. catta (Cavigelli, ), P. troglodytes (Muller & Wrangham, ), Papio anubis (Sapolsky, )). For arboreal primates like howler monkeys, the potential stressors include terrestrial locomotion (an atypical situation that may increase susceptibility to predation) or increased human presence in the fragment (Rangel‐Negrín, Coyohua‐Fuentes, Chavira, Canales‐Espinosa, & Dias, ).…”
Section: Discussionmentioning
confidence: 99%